Prokrastinasi Akademik di Kalangan Mahasiswa - Anisa, Anisa (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This research is a descriptive research that aims to find out the description of academic procrastination carried out by students during online learning. This research is a quantitative descriptive study, using a survey method. Research data collection uses a questionnaire, to collect data regarding academic procrastination carried out by students during online learning. The research population was all fifth semester PGSD students in the 2022-2023 school year, with a sample of 54 respondents. Data on academic procrastination carried out by students were collected through a questionnaire in the form of a Google form, containing 15 questions. The data obtained were then analyzed by descriptive analysis. The results showed that academic procrastination behavior by students was classified into the high category with a percentage of 33.3%.